Editors’s Introduction to the Special Issue on "Frontiers in Network Systems and Applications" - Chojnacki, Andrzej; Grzenda, Maciej; Kowalski, Andrzej; Macukow, Bohdan (Informatica, 2014)
Editors's Introduction to the Special Issue on "Frontiers in Network Systems and Applications"